Transparent Er3+-activated lead fluorogermanate glass ceramics - Rolli, Raffaella; Bueno, Luciano A. [UNESP]; Ribeiro, Sidney J.L. [UNESP]; Messaddeq, Younes [UNESP]; Bettinelli, Marco; Speghini, Adolfo; Ferrari, Maurizio; Armellini, Cristina; Montagna, Maurizio; Righini, Giancarlo C.; Pelli, Stefano (SPIE, the international society for optics and photonics, 2003)
Transparent glass ceramics containing β-PbF2:Er 3+ nanocrystals were obtained through appropriate thermal treatments of a glass of molar composition 60PbGeO3-10PbF2-30CdF 2 doped with 0.5 mol% Er3+. Their optical properties, as well as upconversion processes among erbium ions in the glass and glass ceramic matrix were studied. From absorption spectra, Judd-Ofelt parameters and radiative transition rates for several excited levels were calculated. Emission spectra in the visible and NIR regions were collected, and stimulated emission cross sections were obtained by McCumber theory for the 4F 13/2→4I15/2 transition at 1.5 μm. Red and green upconversion emissions were measured in glass and glass ceramics upon excitation at 980 nm; lifetimes were measured in order to assess the upconversion mechanisms.
Keywords: Emission cross section; Fluorogermanate Erbium; Glass ceramics; Optical materials; Photonics; Upconversion; Amplification; Ceramic materials; Erbium; Heat treatment; Lattice vibrations; Melting; Nanostructured materials; Optical glass; Relaxation processes; Stimulated emission; X ray diffraction analysis; Fluorogermanate erbium; Molar composition; Radiative transition rates